The case of the mysterious voice [compact disc, unabridged] - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2011)
When an odd turn of events brings a parrot to the ranch, Hank ignores the mimicking bird and struggles to keep up with Sally May and Loper's persistent requests to bark louder and dig up the flowers.